Financial Literacy, Financial Risk Tolerance, and Investment Among Postgraduate Students: The Mediating Role of Financial Self-Efficacy - Bella Anggraeni Saputri; Umi Widyastuti; Suparno (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This research was conducted to determine whether financial literacy and risk tolerance influence postgraduate students' investment decisions and to evaluate whether financial self- efficacy can be a bridge between these relationships. The study used a quantitative approach, involving 253 postgraduate students at Jakarta State University who had previously invested or were interested in investing. Information was gathered through surveys and checked with the SEM-PLS method. The results showed how students with better financial understanding tended to be more confident in handling their finances and made better investment decisions. Financial self-efficacy was also shown to play a role in driving investment decisions and acting as a bridge for financial literacy and investment decisions. Meanwhile, risk acceptance didn't give a big impact upon either financial self-eficacy nor investment decisions. In conclusion, the results of this research show that when making investment decisions, financial understanding and trust in their own skills are more influential than mere readiness to face risks. This study indicates that people who are confident in managing their finances are more likely to apply what they know about finance when making investment decisions.